(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
Interaction between Gangleron (spasmolytic and anaesthetizing drug) and human serum albumin (HSA) was studied using UV/vis and fluorescence spectroscopy methods. The quenching mechanism of HSA fluorescence was discussed based on interaction studies carried out at different temperatures (298, 303 and 309 K). Stern-Volmer constant (KSV), quenching rate constant (kq) and activation energy of bimolecular quenching (Еа) were evaluated. UV/vis absorption spectra were used to confirm the quenching mechanism.